Policies and Strategies for Revitalizing America’s Manufacturing Communities - Stettner, Andrew; Yudken, Joel S. (Journal of Management Policy and Practice, 2019)
After decades of decline and political indifference, U.S. manufacturing is getting fresh attention, in national elections and in research about economic disparities between communities and America’s technological leadership. For the past two years, the authors of this report have worked on two-year project, sponsored by The Century Foundation (TCF) and its Bernard L. Schwartz Rediscovering Government Initiative (RGI), to elaborate on the contours of a policy that will not only revitalize the manufacturing industry, but lift the fortunes of struggling communities (urban, rural, and suburban) that have long looked to manufacturing as a source of good paying jobs and economic growth. The two-year project included three major research reports and interactions with nearly 500 stakeholders at community events throughout the industrial Midwest. The paper summarizes the research and (i) discusses why manufacturing remains important, (ii) presents a comprehensive framework for regional industrial policies best practices, and (iii) suggests the key state and federal policies and actions needed to revitalize manufacturing communities. The comprehensive framework identifies two major national policy drivers (trade and government purchasing) and four regional drivers (innovation, industrial retention, workforce and capital) that are all needed for U.S. manufacturing to recapture its economic promise.